Window covering film and flexible display panel including the window covering film
By using a combination of polyamideimide-based resin base layer and hard coating, the existing window covering film has been solved in terms of scratch resistance, impact resistance and flexibility, and has achieved touch and excellent sliding properties like glass, with high hardness, flexibility and excellent mechanical characteristics.
Patent Information
- Application Number
- CN202110397908.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-14
- Filing Date
- 2021-04-14
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-04-14
AI Technical Summary
The existing window covering film has shortcomings in terms of scratch resistance, impact resistance and flexibility, and it is difficult to achieve high hardness and sliding properties corresponding to tempered glass.
The base material layer formed of polyamideimide-based resin and the hard coating layer are used. The hard coating layer uses sulfuric acid paper as the friction material, with a dynamic friction coefficient less than 0.15, and the ratio of the static friction coefficient to the dynamic friction coefficient is within the range of 0.5≤a/b≤1.5.
It realizes the touch and excellent sliding properties like glass, with high surface hardness and flexible surface, and can avoid cracks under repeated bending, and has excellent mechanical properties, wear resistance, stain resistance and warp suppression characteristics.
Smart Images

Figure BDA0003019249250000241 
Figure BDA0003019249250000251
Abstract
Description
Technical Field
[0001] The invention relates to a window covering film and a flexible display panel comprising the window covering film. Background Art
[0002] A thin display device is implemented in the form of a touch screen panel, and is used not only in smart phones and tablet PCs but also in various smart devices such as various wearable devices.
[0003] In such a display device based on a touch screen panel, a window cover made of tempered glass is provided on the display panel in order to protect the display panel from scratches or external impacts.
[0004] However, in recent years, due to the problem that tempered glass is not suitable for weight reduction and is easily subjected to external impact, technology for optical plastic films having flexibility and impact resistance as well as strength or scratch resistance corresponding to tempered glass has been developed.
[0005] This type of plastic material uses polyethylene terephthalate (PET), polyethersulfone (PES), polyethylene naphthalate (PEN), polyacrylate (PAR), polycarbonate (PC), polyimide (PI), polyaramid (PA), etc., but compared with tempered glass, there are problems such as poor hardness, insufficient scratch resistance and poor impact resistance. Therefore, in order to solve this problem, various attempts are being made to form a hard coating on the upper part of the plastic film.
[0006] However, in the case of existing hard coatings, it is not only difficult to achieve high hardness corresponding to tempered glass, but also a large amount of warping (curl) occurs due to shrinkage during curing, and the flexibility is insufficient. Therefore, it has the disadvantage of being unsuitable for use as a protective window substrate for flexible displays. In particular, hard coatings that can impart a glass-like touch and require sliding properties have not yet been fully developed.
[0007] [Prior art literature]
[0008] [Patent Document]
[0009] Korean Patent Publication No. 10-2013-0074167 (July 4, 2013) Summary of the invention
[0010] Technical issues to be solved
[0011] Therefore, an object of the present invention is to provide a window covering film having improved scratch resistance and impact resistance, having a glass-like touch, and also excellent in sliding properties.
[0012] Furthermore, a technical problem of the present invention is to provide a window covering film which does not generate cracks even under repeated bending and has excellent mechanical properties, abrasion resistance, antifouling properties, and warpage suppression properties.
[0013] Technical Solution
[0014] The present invention for achieving the above technical problem provides a window covering film, wherein the window covering film is stacked with: a substrate layer formed of a polyamide-imide-based resin; a hard coating layer formed on at least one side of the substrate layer, and a dynamic friction coefficient measured on the hard coating layer using sulfuric acid paper as a friction material and under a load of 200g, a force of 5N, and a speed of 100mm / min is less than 0.15, and the ratio of the static friction coefficient a to the dynamic friction coefficient b satisfies the following formula 1.
[0015] [Formula 1]
[0016] 0.5≤a / b≤1.5
[0017] More preferably, a window covering film is provided in which the a / b is 1-1.3.
[0018] As an embodiment, the static friction coefficient may be 0.2 or less, and the dynamic friction coefficient may be 0.1 or less.
[0019] As an embodiment, the modulus of the substrate layer according to ASTM D882 may be 3 GPa or more, the elongation at break may be 8% or more, the transmittance measured at 388 nm according to ASTM D1746 may be 5% or more and the total light transmittance measured at 400-700 nm may be 87% or more, the haze may be 2.0% or less, the yellowness index may be 5.0 or less, and the b* value may be 2.0 or less.
[0020] As one embodiment, the base material layer may be formed of a polyamideimide (PAI)-based resin including a fluorine atom and an aliphatic cyclic structure.
[0021] As an embodiment, the substrate layer may be formed of a polyamideimide (PAI)-based resin including a unit derived from a fluorine-based aromatic diamine, a unit derived from an aromatic dianhydride, a unit derived from an alicyclic dianhydride, and a unit derived from an aromatic diacid chloride.
[0022] As an embodiment, the thickness of the substrate layer may be 10-500 μm, and the thickness of the hard coating layer may be 1-50 μm.
[0023] As an embodiment, the pencil hardness of the hard coating layer may be 4H or more, and the water contact angle may be 80° or more.
[0024] As an embodiment, the hard coating layer may be formed of a composition for forming a hard coating layer, the composition for forming a hard coating layer comprising a (meth)acrylic silicone resin and a multifunctional (meth)acrylate-based compound.
[0025] As an embodiment, the warpage amount of each vertex of a square sample of the window cover film, which is a sample cut so that each side has a length of 10 cm and is inclined at an angle of 45° with respect to the MD direction of the film, may be 5 mm or less.
[0026] As an embodiment, when evaluating dynamic bending characteristics, the window cover film may not generate cracks at 30,000 to 200,000 times.
[0027] Another embodiment of the present invention provides a flexible display panel including the window cover film of the above one embodiment.
[0028] Beneficial Effects
[0029] The window cover film of the present invention has a glass-like touch, is excellent in sliding properties, has high surface hardness and flexibility, and is excellent in bending properties.
[0030] Furthermore, even if deformation occurs repeatedly, the hard coat layer and the window cover film do not substantially undergo semi-permanent deformation or damage, and have excellent restoring power to return to the original shape.
[0031] Therefore, it is possible to provide a window covering film that can be used for a display having a curved shape or a foldable device, etc.
[0032] Furthermore, the durability and long-term life of the flexible display can be ensured.
[0033] In addition, physical and chemical stability can be ensured even under high temperature and high humidity conditions.
[0034] Furthermore, the window covering film according to one embodiment of the present invention may provide a window covering film having excellent stain resistance and improved wear resistance, unlike the prior art.
[0035] The window covering film of the present invention can further improve the flexibility and mechanical strength of the window covering film by combining the polyamideimide-based substrate layer and the hard coating layer. DETAILED DESCRIPTION
[0036] The present invention will be described in more detail below. However, the following embodiment is only a reference for describing the present invention in detail, and the present invention is not limited thereto, and the present invention can be implemented through various embodiments.
[0037] In addition, unless otherwise defined, all technical terms and scientific terms have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only used to effectively describe specific embodiments and are not intended to limit the present invention.
[0038] Furthermore, unless otherwise specifically stated, singular forms used in the specification and claims also include plural forms.
[0039] In addition, unless otherwise specifically described to the contrary, the description that a part “includes” or “comprises” a certain constituent element means that other constituent elements may also be included, rather than excluding other constituent elements.
[0040] The "film" in the present invention is obtained by coating the "polyamide-imide-based resin solution" on a substrate, drying it, and peeling it off, and it may be stretched or unstretched.
[0041] In the present invention, “warping” may refer to bending deformation of a film, and “warping amount” may refer to the vertical height from the lowest position of the film to the position where the film is warped when the warped film is placed on a flat surface.
[0042] The term "warping suppression property" used in this specification may refer to a property showing a small "warping amount".
[0043] In the present invention, the "dynamic bending property" may mean that even if the window cover film is repeatedly deformed (eg, folded and unfolded), the deformed portion (eg, the folded portion) will not be permanently deformed and / or damaged.
[0044] Hereinafter, the present invention will be described.
[0045] The inventors of the present invention have conducted many studies to solve the above-mentioned technical problems and found that as long as the ratio of the static friction coefficient to the dynamic friction coefficient satisfies a specific range, a window cover film with anti-fingerprint properties, a glass-like touch and excellent sliding properties can be provided, thereby completing the present invention.
[0046] Specifically, the inventors of the present invention found that when sulfuric acid paper is used as a friction material and the dynamic friction coefficient (b) measured under a load of 200g, a force of 5N, and a speed of 100mm / min is less than 0.15, and the ratio of the static friction coefficient (a) to the dynamic friction coefficient (b) satisfies the range of 0.5≤a / b≤1.5, a window covering film having a glass-like touch and excellent sliding properties can be provided, thereby completing the present invention.
[0047] In addition, the inventors of the present invention have discovered that by forming a substrate layer formed of a polyamideimide-based resin and a hard coating layer on at least one side of the substrate layer, a window covering film can be provided, wherein the window covering film has significantly less warping due to the combination of the polyamideimide-based substrate layer and the hard coating layer, and has a glass-like touch, excellent sliding properties, high surface hardness and flexibility, and excellent bending properties, thereby completing the present invention.
[0048] Furthermore, in the present invention, in the case of a polyamideimide-based polymer having a fluorine-substituted polyamide block and having an alicyclic structure, a film having more excellent touch and flexibility, excellent optical properties and more excellent bending properties, and less warping can be provided, and is therefore more preferred.
[0049] The window covering film of one embodiment of the present invention is stacked with: a substrate layer formed of a polyamide-imide-based resin; and a hard coating layer formed on at least one side of the substrate layer. The layers are stacked in a directly connected manner to achieve all the desired physical properties, so it is more preferred. Other layers may be provided between the layers or on the hard coating layer as needed.
[0050] The window cover film according to one embodiment of the present invention has a feature of greatly improving mechanical physical properties and dynamic bending characteristics through chemical bonding between the substrate layer and the hard coating layer.
[0051] In addition, chemical bonding between these layers can provide a glass-like touch.
[0052] Specifically, the excellent or improved dynamic bending characteristics means that even if the window covering film is repeatedly deformed, specifically, even if the window covering film is repeatedly folded and unfolded, it will not be deformed and will not crack.
[0053] More specifically, when the dynamic bending characteristics are measured, no cracks are generated at more than 30,000 times, preferably more than 100,000 times, and more preferably from 30,000 times to 200,000 times. The cracks may refer to fine cracks.
[0054] The term "fine crack" used in this specification may refer to a crack of a size that cannot be generally observed by visual inspection. The fine crack may refer to a crack of a size of 0.5 μm or more in width and 10 μm or more in length, for example, which can be observed under a microscope.
[0055] Specifically, the present invention relates to a window covering film, in which: a base layer formed of a polyamide-imide-based resin; and a hard coating layer formed on at least one side of the base layer are stacked.
[0056] In the window covering film of the present invention, the dynamic friction coefficient (b) measured on the hard coating layer using parchment paper under a load of 200 g, a force of 5 N, and a speed of 100 mm / min is less than 0.15, and the ratio of the static friction coefficient (a) to the dynamic friction coefficient (b) can satisfy the following formula 1.
[0057] At this time, the dynamic friction coefficient and the static friction coefficient are measured according to ASTM D1894, and are measured using a Friction Tester device (TOYOSEIKI Corporation, TR-2).
[0058] [Formula 1]
[0059] 0.5≤a / b≤1.5
[0060] The ratio (a / b) of the static friction coefficient (a) to the dynamic friction coefficient (b) may preferably be 0.6-1.4, more preferably 0.8-1.3, and most preferably 0.9-1.2.
[0061] Within the above range, durability and surface strength like glass can be provided, and a tactile feeling like touching real glass can be provided to the user.
[0062] Hereinafter, the configuration of each layer of the present invention will be described in detail.
[0063] <Base material layer>
[0064] The base material layer has excellent optical and mechanical properties, and can be formed of a material having elasticity and restoring force.
[0065] In one embodiment of the present invention, the thickness of the substrate layer may be 10-500 μm, 20-250 μm or 30-100 μm.
[0066] In one embodiment of the present invention, the modulus of the substrate layer according to ASTM D882 may be 3 GPa or more, 4 GPa or more, or 5 GPa or more, the elongation at break may be 8% or more, 12% or more, or 15% or more, the transmittance measured at 388 nm according to ASTM D1746 may be 5% or more or 5-80%, and the total light transmittance measured at 400-700 nm may be 87% or more, 88% or more, or 89% or more, the haze according to ASTM D1003 may be 2.0% or less, 1.5% or less, or 1.0% or less, the yellowness index according to ASTM E313 may be 5.0 or less, 3.0 or less, or 0.4-3.0, and the b* value may be 2.0 or less, 1.3 or less, or 0.4-1.3.
[0067] In one embodiment of the present invention, the substrate layer is a polyamide-imide resin.
[0068] Furthermore, more preferably, the base material layer of the present invention may be a polyamide-imide-based resin containing fluorine atoms and an aliphatic cyclic structure, thereby having excellent mechanical physical properties and dynamic bending characteristics.
[0069] As a more specific example, the base material layer may include a polyamideimide-based resin derived from a fluorine-based aromatic diamine, an aromatic dianhydride, an alicyclic dianhydride, and an aromatic diacid chloride.
[0070] In one embodiment of the present invention, as an example of the polyamide-imide-based resin containing fluorine atoms and an aliphatic cyclic structure, an amine-terminated polyamide oligomer derived from a first fluorine-based aromatic diamine and an aromatic diacid chloride can be prepared, and the amine-terminated polyamide oligomer is polymerized with a monomer derived from a second fluorine-based aromatic diamine, an aromatic dianhydride and an alicyclic dianhydride and imidized to prepare a polyamide-imide polymer. In the case of the polymer, the purpose of the present invention can be better achieved, so it is preferred, but not necessarily limited to this.
[0071] The first fluorine-based aromatic diamine and the second fluorine-based aromatic diamine may be the same as or different from each other.
[0072] In one embodiment of the present invention, as described above, when an amine-terminated oligomer containing an amide structure formed in the polymer chain by an aromatic diacid chloride is used as a monomer of the diamine, the optical physical properties can be improved, in particular, the mechanical strength including the modulus can be improved, and the dynamic bending characteristics can be further improved, so it is preferred, but not necessarily limited to this.
[0073] In one embodiment of the present invention, when the polyamide oligomer block is fluorine-substituted as described above, the diamine monomer comprising the amine-terminated fluorine-substituted poly-oligomer and the second fluorine-based aromatic diamine and the dianhydride monomer comprising the aromatic dianhydride and alicyclic dianhydride of the present invention can be preferably used in a molar ratio of 1:0.9-1.1, and more preferably can be used in a molar ratio of 1:1.
[0074] In addition, when the amine-terminated polyamide oligomer contains more than 30 mol %, preferably more than 50 mol %, and more preferably more than 70 mol %, relative to the total diamine monomers mentioned above, it is more conducive to satisfying the mechanical physical properties, yellowness index, and optical properties of the present invention, and when providing the polyamide-imide film with surface energy difference of the present invention, the selectivity of the coating solvent can be improved by the diversity of solubility, but the content of the amine-terminated polyamide oligomer is not particularly limited.
[0075] In addition, there is no particular restriction on the composition ratio of aromatic dianhydride and alicyclic dianhydride, but in consideration of achieving the transparency, yellowness index, mechanical physical properties, etc. of the present invention, it is preferably used in a ratio of 30-80 mol %:70-20 mol %, but it is not necessarily limited thereto.
[0076] Furthermore, another example of the polyamideimide-based resin containing fluorine atoms and an aliphatic cyclic structure in the present invention may be a polyamideimide-based resin in which fluorine-based aromatic diamine, aromatic dianhydride, alicyclic dianhydride and aromatic diacid chloride are mixed and polymerized and imidized.
[0077] This resin has a random copolymer structure and can be prepared as follows, that is, relative to 100 moles of diamine, more than 40 moles of aromatic diacid chloride can be used, preferably 50-80 moles of aromatic diacid chloride can be used, the content of aromatic dianhydride can be 10-50 moles, the content of alicyclic dianhydride can be 10-60 moles, and the sum of diacid chloride and dianhydride is polymerized at a molar ratio of 1:0.9-1.1 relative to the diamine monomer, preferably at a molar ratio of 1:1.
[0078] Compared with the block polyamide-imide resin, the random polyamide-imide of the present invention has different optical properties such as transparency, mechanical physical properties, and solvent sensitivity due to surface energy differences, but it can also fall within the scope of the present invention.
[0079] In one embodiment of the present invention, the fluorine-based aromatic diamine component can be mixed with 2,2'-bis(trifluoromethyl)-benzidine and other known aromatic diamine components and used, but 2,2'-bis(trifluoromethyl)-benzidine can also be used alone. By using the fluorine-based aromatic diamine as described above, the optical properties of the polyamideimide-based film can be improved, and the yellow index can be improved. In addition, by increasing the tensile modulus of the polyamideimide-based film, the mechanical strength of the window cover film can be increased, and the dynamic bending characteristics can be further improved.
[0080] The aromatic dianhydride may be at least one or more of 4,4'-hexafluoroisopropylidene diphthalic anhydride (6FDA), biphenyltetracarboxylic anhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA), sulfonyl diphthalic anhydride (SO2DPA), (isopropylidene diphenoxy) di(phthalic anhydride) (6HDBA), 4-(2,5-dioxytetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic anhydride (TDA), 1,2,4,5-benzenetetracarboxylic anhydride (PMDA), benzophenonetetracarboxylic anhydride (BTDA), bis(3,4-dicarboxyphenyl)dimethylsilane dianhydride (SiDA) and bis(dicarboxyphenoxy)diphenyl sulfide dianhydride (BDSDA), but the present invention is not limited thereto.
[0081] The alicyclic dianhydride that can be used is, for example, any one selected from 1,2,3,4-cyclobutanetetracarboxylic dianhydride (CBDA), 5-(2,5-dioxotetrahydrofuranyl)-3-methylcyclohexene-1,2-dicarboxylic dianhydride (DOCDA), bicyclo[2.2.2]oct-7-ene-2,3,5,6-tetracarboxylic dianhydride (BTA), bicyclooctene-2,3,5,6-tetracarboxylic dianhydride (BODA), 1,2,3,4-cyclopentanetetracarboxylic dianhydride (CPDA), 1,2,4,5-cyclohexanetetracarboxylic dianhydride (CHDA), 1,2,4-tricarboxy-3-carboxymethylcyclopentane dianhydride (TMDA), 1,2,3,4-tetracarboxycyclopentane dianhydride (TCDA) and derivatives thereof, or a mixture of two or more thereof.
[0082] In one embodiment of the present invention, when an amide structure is formed in a polymer chain by an aromatic diacid chloride, optical physical properties can be improved, and in particular, mechanical strength including modulus can be greatly improved, and dynamic bending properties can be further improved.
[0083] The aromatic dicarboxylic dichloride may be any one selected from the group consisting of isophthaloyl dichloride (IPC), terephthaloyl dichloride (TPC), [1,1'-Biphenyl]-4,4'-dicarbonyl dichloride (BPC), 1,4-naphthalenedicarboxylic dichloride (NPC), 2,6-naphthalene dicarboxylic dichloride (NTC), 1,5-naphthalene dicarboxylic dichloride (NEC) and derivatives thereof, or a mixture of two or more thereof, but is not limited thereto.
[0084] Hereinafter, a method for producing a film as a base material layer will be exemplified without limitation.
[0085] In one embodiment of the present invention, the substrate layer can be manufactured by coating a "polyamideimide resin solution" containing a polyamideimide resin and a solvent on a substrate and then drying or drying and stretching. That is, the substrate layer can be manufactured by a solution casting method.
[0086] As an example, the substrate layer can be manufactured by a method including the following steps: reacting a fluorine-based aromatic diamine and an aromatic diacid chloride to prepare an oligomer; reacting the prepared oligomer with a fluorine-based aromatic diamine, an aromatic dianhydride, and an alicyclic dianhydride to prepare a polyamic acid solution; imidizing the polyamic acid solution to prepare a polyamideimide resin; and coating the polyamideimide solution to manufacture a film, wherein the polyamideimide solution is obtained by dissolving the polyamideimide resin in an organic solvent.
[0087] Hereinafter, each step will be described by taking the case of producing a block polyamide-imide film as an example.
[0088] The step of preparing the oligomer may include the steps of: reacting a fluorine-based aromatic diamine with an aromatic diacid chloride in a reactor; and purifying and drying the obtained oligomer.
[0089] In this case, the fluorine-based aromatic diamine is added at a molar ratio of 1.01-2 relative to the aromatic diacid chloride, thereby preparing an amine-terminated polyamide oligomer monomer. The molecular weight of the oligomer monomer is not particularly limited, for example, when the weight average molecular weight is in the range of 1000-3000 g / mol, more excellent physical properties can be obtained. At this time, by polymerizing the oligomer in the presence of pyridine to suppress side reactions, a resin with more excellent physical properties can be prepared.
[0090] Furthermore, in order to introduce an amide structure, it is preferred to use an aromatic carbonyl halide monomer such as terephthaloyl chloride or isophthaloyl chloride rather than terephthalate or terephthalic acid itself. Although this is not clear, it is believed that the chlorine element affects the physical properties of the film.
[0091] Then, the step of preparing the polyamic acid solution may be achieved by a solution polymerization reaction of reacting the prepared oligomer with a fluorine-based aromatic diamine, an aromatic dianhydride, and an alicyclic dianhydride in an organic solvent.
[0092] At this time, the organic solvent used for the polymerization reaction can be, for example, any one or more polar solvents selected from dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethyl cellosolve, methyl cellosolve, acetone, ethyl acetate, m-cresol, etc.
[0093] Then, the imidization step in the present invention can be carried out by chemical imidization, more preferably, the polyamic acid solution is chemically imidized using pyridine and acetic anhydride. The reaction temperature is below 150°C, preferably below 100°C, specifically, at a low temperature of 50-150°C, and the imidization can be carried out using an imidization catalyst and a dehydrating agent.
[0094] Such chemical imidization is preferred because it can impart uniform mechanical properties to the entire film, compared to an imidization reaction performed by heat at a high temperature.
[0095] The imidization catalyst may be any one or more selected from pyridine, isoquinoline and β-quinoline. In addition, the dehydrating agent may be any one or more selected from acetic anhydride, phthalic anhydride and maleic anhydride, but is not necessarily limited thereto.
[0096] In addition, the polyamide-imide resin can be prepared by mixing additives such as flame retardants, tackifiers, inorganic particles, antioxidants, UV inhibitors and plasticizers into the polyamic acid solution.
[0097] The weight average molecular weight of the polyamide-imide resin in the present invention may be 200,000 g / mol or more, preferably 300,000 g / mol or more, and more preferably 300,000-400,000 g / mol, but the weight average molecular weight of the polyamide-imide resin is not particularly limited. Within the above range, after the film is restricted, when a hard coating is formed on the layer, the occurrence of warping is suppressed, and more excellent dynamic bending characteristics can be provided by chemical bonding with the hard coating, so it is preferred, but not necessarily limited thereto.
[0098] In the present invention, in the production of the membrane, polyamideimide may be prepared by the imidization step, purified, and dissolved in a solvent such as N,N-dimethylacetamide (DMAc) to prepare a solution for producing the membrane.
[0099] In the steps of the present invention, the polyamide-imide solution can be coated on the substrate and then dried in a drying step divided into a drying area, or a stretching step can be added after or before drying to produce the polyamide-imide solution. A heat treatment step can also be added after the drying and / or stretching steps to produce the polyamide-imide solution. The substrate for casting the solution can be glass, stainless steel or other substrate films, etc., but the substrate is not particularly limited. The polyamide-imide of the present invention can be coated on the substrate layer by a die coater, air knife coating, reverse roll coating, spraying, blade coating, casting, gravure coating, spin coating, etc., but conventional solution casting methods can be used without limitation.
[0100] <Hard Coating>
[0101] The hard coat layer of the present embodiment is formed in order to protect the base layer having excellent optical and mechanical properties from external physical and chemical damage.
[0102] In one embodiment of the present invention, the hard coating layer may have a thickness of 1 to 50% of the total thickness of the window covering film including the substrate film and the hard coating layer.
[0103] The hard coating layer in the present invention has excellent hardness and can maintain optical properties. The thickness of the hard coating layer can be 1-50 μm, more preferably 1-30 μm, the pencil hardness can be above 2H, above 3H or above 4H, more preferably 4H to 9H, and when scratch evaluation is performed using steel wool (#0000, LIBERON), no scratches are generated at 10 times / 1Kgf, 20 times / 1Kgf or 30 times / 1Kgf, and the water contact angle can be above 80°, above 90° or above 100°.
[0104] As an example of a composition for providing a hard coating layer of the present invention that imparts the above-mentioned properties, there can be cited a composition for forming a hard coating layer comprising a (meth)acrylic silicone resin and a multifunctional (meth)acrylate compound, which can be formed by coating the composition on the upper part of a substrate layer forming a window cover film and curing it.
[0105] In one embodiment of the present invention, the (meth)acrylic silicone resin refers to a silicone resin having a (meth)acrylate group, and the (meth)acrylate can be an alicyclic (meth)acrylate group, an aliphatic (meth)acrylate group, an aromatic (meth)acrylate group or a mixture thereof, and preferably can be a silsesquioxane having a (meth)acrylate (hereinafter referred to as a (meth)acrylate silicone resin).
[0106] The weight average molecular weight of the (meth)acrylate siloxane resin of the present invention is 500-30000. In terms of ensuring both high hardness and processability, it is preferably 1000-20000, and more preferably 5000-15000. When a (meth)acrylate siloxane resin having a polydispersity index (PDI) of 2.0-4.0 is used, the two physical properties of hardness and ductility of the coating can be satisfied simultaneously, and it has excellent coating properties and surface smoothness, so it is preferred, but not necessarily limited to this.
[0107] The composition for forming a hard coating layer of the present invention can provide a dynamic friction coefficient and a static friction coefficient satisfying Formula 1 by chemically bonding with a polyamide-imide-based substrate layer, and can impart a glass-like touch, and can significantly improve hardness. In addition, the flexibility is significantly improved, so that the occurrence of bending deformation and warping can be suppressed.
[0108] [Formula 1]
[0109] 0.5≤a / b≤1.5
[0110] (Ratio (a / b) of static friction coefficient (a) to dynamic friction coefficient (b))
[0111] The (meth)acrylate siloxane resin of the present invention may be prepared by a single alkoxysilane having a (meth)acrylate group or by a hydrolysis and condensation reaction between an alkoxysilane having a (meth)acrylate group and a different kind of alkoxysilane in the presence of water.
[0112] There is no particular limitation on the catalyst used in the reaction as long as it is a commonly used catalyst. For example, acid catalysts such as hydrochloric acid, acetic acid, hydrogen fluoride, nitric acid, sulfuric acid, chlorosulfonic acid, iodic acid, and pyrophosphoric acid; base catalysts such as ammonia, potassium hydroxide, sodium hydroxide, barium hydroxide, imidazole, n-butylamine, di-n-butylamine, tri-n-butylamine, ammonium perchlorate, and tetramethylammonium hydroxide; and ion exchange resins such as Amberlite IRA-400 and IRA-67 can be used, and any combination thereof can be selected and used.
[0113] There is no particular limitation on the amount of the catalyst, but in the case of acid catalysts and base catalysts, 0.0001-0.01 parts by weight can be added relative to 100 parts by weight of alkoxysilane, and in the case of ion exchange resins, 1-10 parts by weight can be added relative to 100 parts by weight of alkoxysilane, but it is not limited thereto.
[0114] The hydrolysis and condensation reaction may be carried out by stirring at room temperature for about 12 hours to about 7 days, but in order to promote the reaction, it may be stirred at about 60° C. to about 100° C. for about 2 hours to about 72 hours, but is not limited thereto.
[0115] In addition, alcohol and water are generated as byproducts during the reaction, and by removing the alcohol and water, the reverse reaction can be reduced and the forward reaction can be induced, thereby adjusting the reaction rate. In addition, at the end of the reaction, the alcohol and water remaining in the siloxane resin can be removed by applying a condition of about 60° C. to about 100° C. under reduced pressure for about 10 minutes to about 60 minutes, but it is not limited thereto.
[0116] The alkoxysilane having a (meth)acrylate group used in the preparation of the (meth)acrylate siloxane resin according to one specific embodiment of the present invention may be exemplified by the following Chemical Formula 1.
[0117] [Chemical formula 1]
[0118] R 1 n Si(OR 2 ) 4-n
[0119] (Where R 1 is a (meth)acrylate cycloalkyl group having 3 to 6 carbon atoms or a linear or branched alkyl group having 1 to 6 carbon atoms substituted with an oxirane group, R2 is a linear or branched alkyl group having 1 to 7 carbon atoms, and n is an integer of 1 to 3.
[0120] Examples of the alkoxysilane represented by the chemical formula 1 include 3-acryloxypropyltrimethoxysilane and 3-methacryloxypropyltrimethoxysilane, and the like, but the alkoxysilane is not particularly limited. These may be used alone or in combination of two or more.
[0121] In a specific embodiment of the present invention, the (meth)acrylate siloxane resin can be prepared by a single alkoxysilane having (meth)acrylate, and can also be prepared by a hydrolysis and condensation reaction between an alkoxysilane having (meth)acrylate and a different type of alkoxysilane, but is not limited thereto.
[0122] The different types of alkoxysilanes may use one or more selected from the alkoxysilanes represented by the following Chemical Formula 2:
[0123] [Chemical formula 2]
[0124] R 3 m Si(OR 4 ) 4-m ;
[0125] (Where R 3 is an alkyl group having 1 to 20 carbon atoms, a cycloalkyl group having 3 to 8 carbon atoms, an alkenyl group having 3 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, or an aryl group having 6 to 20 carbon atoms, and may contain one or more functional groups selected from acryloyl, methacryloyl, halogen, amino, mercapto, ether, ester, carbonyl, carboxyl, vinyl, nitro, sulfone, and alkyd groups, R 4 is a linear or branched alkyl group having 1 to 7 carbon atoms, and m is an integer of 0 to 3.
[0126] The alkoxysilane represented by the chemical formula 2 can be used alone, for example, selected from N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltrimethoxysilane, N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltriethoxysilane, N-(3-acryloxy-2-hydroxypropyl)-3-aminopropyltripropoxysilane, 3-acryloxypropylmethylbis(trimethoxy)silane, 3-acryloxypropyltriethoxysilane, 3-acryloxypropyltripropoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropyltripropoxysilane, etc., or a mixture of two or more thereof, and the alkoxysilane is not particularly limited.
[0127] As an embodiment, the composition for forming a hard coating layer may further include a (meth)acrylate-based compound. The (meth)acrylate-based compound may also be a (meth)acrylate-based compound having one (meth)acrylate functional group, or a multifunctional (meth)acrylate having two or more (meth)acrylate functional groups may be used to induce a crosslinking reaction. By selectively adding the (meth)acrylate-based compound, it is possible to have excellent hardness while further improving the glass-like touch and sliding properties, and therefore it is preferred.
[0128] The (meth)acrylate-based compound of the present invention refers to a compound containing a (meth)acrylate group, and (meth)acrylate refers to acrylate or methacrylate.
[0129] The (meth)acrylate compound of the present invention is not particularly limited as long as it contains a (meth)acrylate group, and may contain at least one of a (meth)acrylate monomer and a (meth)acrylate oligomer. In this specification, an oligomer refers to a case where the repeating unit is 2 to 20 or less.
[0130] Without departing from the purpose of the present invention, the (meth)acrylate compound is not particularly limited, and specific examples thereof include 2-ethylhexyl acrylate, octadecyl acrylate, isodecyl acrylate, 2-phenoxyethyl acrylate, lauryl acrylate, octadecyl acrylate, behenyl acrylate, tridecyl methacrylate, nonylphenol ethoxy monoacrylate, β-carboxyethyl acrylate, isobornyl acrylate, tetrahydrofuranyl acrylate, tetrahydrofuranyl methacrylate, 4-butylcyclohexyl acrylate, dicyclopentenyl acrylate, Acid esters, dicyclopentenyloxyethyl acrylate, ethoxyethoxyethyl acrylate, ethoxylated monoacrylate, 1,6-hexanediol diacrylate, triphenyl glycol diacrylate, butanediol diacrylate, 1,3-butanediol dimethacrylate, 1,6-hexanediol dimethacrylate, neopentyl glycol diacrylate, ethylene glycol dimethacrylate, diethylene glycol diacrylate, diethylene glycol dimethacrylate, tetraethylene glycol diacrylate, tetraethylene glycol dimethacrylate, triethylene glycol diacrylate, triethylene glycol dimethyl Acrylates, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, dipropylene glycol diacrylate, ethoxylated neopentyl glycol diacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol triacrylate, pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, dipentaerythritol pentamethacrylate, dipentaerythritol hexamethacrylate, phosphazene acrylate, phosphazene methacrylate Acid esters, ethoxylated triacrylates, tris(2-hydroxyethyl)isocyanurate triacrylates, dipentaerythritol pentaacrylates, ditrimethylolpropane tetraacrylates, alkoxylated tetraacrylates, etc., preferably pentaerythritol triacrylate, pentaerythritol trimethacrylate, pentaerythritol tetramethacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, dipentaerythritol pentamethacrylate, dipentaerythritol hexamethacrylate, phosphazene acrylate, phosphazene methacrylate, etc. These can be used alone or in combination of two or more.
[0131] Without departing from the purpose of the present invention, there is no particular limitation on the (meth)acrylate oligomer, and specific examples thereof include polyester (meth)acrylate, polyurethane (meth)acrylate, epoxy (meth)acrylate, polyether (meth)acrylate, etc. These can be used alone or in combination of two or more.
[0132] In order to have excellent hardness and bending characteristics, the (meth)acrylate-based compound preferably contains 6 to 15 (meth)acrylate groups in the molecule, and thus an oligomer may be used in this regard, and more preferably urethane (meth)acrylate may be used.
[0133] The composition for forming a hard coating layer of the present invention may further contain a conventional thermal initiator or photoinitiator.
[0134] The photoinitiator may be used without limitation as long as it can initiate the photopolymerization of the (meth)acrylate siloxane resin and the (meth)acrylate-based compound. Examples of the photoinitiator include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin n-butyl ether, benzoin isobutyl ether, acetophenone, hydroxydimethylacetophenone, dimethylaminoacetophenone, dimethoxy-2-phenylacetophenone, 3-methylacetophenone, 2,2-dimethoxy-2-phenylacetophenone, 2,2-diethoxy-2-phenylacetophenone, 4-chloroacetophenone, 4,4-dimethoxyacetophenone, 2-hydroxy-2-methyl-1-phenylpropane-1-one, 4-hydroxycyclophenyl ketone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl-1-[4- [(methylthio)phenyl]-2-morpholinyl-1-propanone, 4-(2-hydroxyethoxy)phenyl-2-(hydroxy-2-propyl)ketone, benzophenone, p-phenylbenzophenone, 4,4-diaminobenzophenone, 4,4'-diethylaminobenzophenone, dichlorobenzophenone, anthraquinone, 2-methylanthraquinone, 2-ethylanthraquinone, 2-tert-butylanthraquinone, 2-aminoanthraquinone, 2-methylthioxanthone, 2-ethylthioxanthone, 2-chlorothioxanthone, 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, benzyl dimethyl ketal, benzophenone benzyl dimethyl ketal, acetophenone dimethyl ketal, p-dimethylaminobenzoate, 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide, fluorene, triphenylamine, carbazole, etc. These can be used alone or in combination of two or more.
[0135] The content of the photoinitiator is not particularly limited, and for example, the photoinitiator may be included in an amount of 0.1 to 20 wt % based on the total weight of the composition for forming the hard coating layer.
[0136] The composition for forming a hard coat layer of the present invention may further contain a solvent.
[0137] The solvent of the present invention is not particularly limited, and solvents known in the art can be used, for example, alcohol-based solvents (methanol, ethanol, isopropanol, butanol, methyl cellosolve, ethyl cellosolve, etc.), ketone-based solvents (methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, dipropyl ketone, cyclohexanone, etc.), hexyl solvents (hexane, heptane, octane, etc.), phenyl solvents (benzene, toluene, xylene, etc.), etc. can be used. These can be used alone or in combination of two or more.
[0138] The content of the solvent of the present invention is not particularly limited, for example, the total weight of the composition for forming the hard coating layer may contain 10-60% by weight of the solvent. When the content of the solvent is within the above range, a suitable viscosity is maintained, so the operability is excellent, the thickness of the coating film can be easily adjusted, and the process speed can be increased.
[0139] According to needs, the composition for forming a hard coating layer of the present invention may further include a slip agent to improve winding efficiency, anti-blocking property, abrasion resistance, and scratch resistance.
[0140] There is no particular restriction on the type of the slip agent, for example, wax-based slip agents such as polyethylene wax, paraffin wax, synthetic wax or montan wax; synthetic resin-based slip agents such as silicone-based resins and fluorine-based resins, etc. can be cited. These can be used alone or in combination of two or more. There is no particular restriction on the content of the slip agent, for example, the total weight of the composition for forming the hard coating layer can contain 0.1-5% by weight of the slip agent. When the content of the slip agent is within the above range, excellent anti-blocking, friction resistance and scratch resistance are imparted, and excellent transparency can also be maintained.
[0141] Furthermore, additives such as an antioxidant, an ultraviolet (UV) absorber, a light stabilizer, a thermal polymerization inhibitor, a leveling agent, a surfactant, a lubricant, and an antifouling agent may be contained as necessary.
[0142] Hereinafter, the method for forming the hard coat layer will be described in detail.
[0143] In one embodiment of the present invention, the hard coating layer can be formed by applying the above-mentioned composition for forming the hard coating layer on the upper surface or lower surface of the substrate layer and curing. The curing can be carried out by heat curing and / or light curing, and methods well known in the art can be used.
[0144] The coating can be performed by a known method such as die coater, air knife coating, reverse roll coating, spray coating, knife coating, casting, gravure coating, spin coating, etc.
[0145] The curing method is not particularly limited, and for example, it may be performed by light curing or heat curing alone, or by heat curing followed by light curing, or light curing followed by heat curing.
[0146] In one embodiment of the present invention, by using the composition for forming a hard coating layer, the substrate layer can be physically protected, the mechanical physical properties can be further improved, and the dynamic bending characteristics can be further improved, and the occurrence of warping can be significantly reduced.
[0147] Specifically, a window covering film can be provided, which does not produce cracks even if the dynamic bending characteristics are repeated more than 30,000 times, more specifically 30,000 to 200,000 times, and more preferably more than 200,000 times. In addition, a window covering film can be provided, which has a warpage of 5 mm or less, preferably 4 mm or less, more preferably 3 mm or less, and more preferably 0-2 mm when measured by the evaluation method described below.
[0148] In one embodiment of the present invention, a plurality of the base layer and the hard coating layer may be laminated.
[0149] For example, a plurality of substrate layers and a plurality of hard coating layers may be alternately stacked. In addition, a hard coating layer may be provided on one side or both sides of the substrate layer.
[0150] In one embodiment of the present invention, when a substrate layer formed of a polyamide-imide-based resin and a hard coating layer formed on at least one side of the substrate layer are stacked, uniform physical properties are exhibited through chemical bonding between the substrate layer and the hard coating layer, so that the entire film area can exhibit uniform physical properties and can be imparted with glass-like durability and touch.
[0151] More specifically, the dynamic friction coefficient measured on the hard coating layer using sulfuric acid paper as a friction material and under a load of 200g, a force of 5N, and a speed of 100mm / min is less than 0.15 or less than 0.1, and the ratio of the static friction coefficient a to the dynamic friction coefficient b can satisfy the following formula 1.
[0152] [Formula 1]
[0153] 0.5≤a / b≤1.5
[0154] More specifically, the ratio a / b of the static friction coefficient a to the dynamic friction coefficient b may be 0.6-1.4, more preferably 0.8-1.3, and further preferably 0.9-1.2.
[0155] Within the above range, durability and surface strength like glass can be provided, and a tactile feeling like touching real glass can be provided to the user.
[0156] The static friction coefficient of the window cover film may be 0.2 or less, 0.15 or less, 0.12 or less, or 0.01 to 0.12. In addition, the dynamic friction coefficient may be 0.15 or less, 0.11 or less, or 0.01 to 0.1. Within the above range, the sliding property is excellent and the touch like glass can be exhibited, which is more preferred.
[0157] In addition, as described above, the window cover film can provide a tactile feeling like touching glass, and can provide a window cover film having excellent durability and a warping suppression property. The “warping suppression property” can mean that the amount of warping is significantly small.
[0158] The warpage amount represents the vertical height from the lowest position (e.g., center) of the film to each vertex of a square sample of the window cover film, wherein the square sample is a sample cut into a square inclined at an angle of 45° relative to the MD direction and each side is 10 cm.
[0159] When the warpage of a sample tilted at an angle of 45° with respect to the MD direction is measured, the warpage at each vertex indicates the warpage in the MD direction and in a direction perpendicular to the MD direction, so that the warpage in each direction can be distinguished.
[0160] In some embodiments, the warping amount of the window covering film may be 5 mm or less, preferably 4 mm or less, more preferably 3 mm or less, and further preferably 0-2 mm.
[0161] <Flexible display panel>
[0162] An embodiment of the present invention may provide a flexible display panel or a flexible display device including the window cover film of one embodiment described above.
[0163] At this time, the window cover film can be used as the outermost window substrate of the flexible display device. The flexible display device can be a conventional liquid crystal display device, an electroluminescent display device, a plasma display device, a field emission display device, or other image display devices.
[0164] Hereinafter, the present invention will be described in more detail based on Examples and Comparative Examples. However, the following Examples and Comparative Examples are merely examples for describing the present invention in more detail, and the present invention is not limited to the following Examples and Comparative Examples.
[0165] 1) Friction coefficient
[0166] According to ASTM D1894, the film was cut into a width of 50 mm and a length of 150 mm, and then fixed on a friction measuring instrument (TOYOSEIKI Corporation, TR-2), using parchment paper as a friction material, and then a distance of 100 mm was measured under a load of 200 g, a force (Load) of 5 N, and a speed of 100 mm / min.
[0167] 2) Touch
[0168] Thirty panelists touched the surface of the manufactured window film with their hands and evaluated how well they felt like touching real glass, with 10 being the full score. The total scores of the 30 panelists were converted to an average value.
[0169] 3) Weight average molecular weight
[0170] <Weight Average Molecular Weight of Film>
[0171] The membrane was dissolved in DMAc eluent containing 0.05M LiBr and measured. GPC used a Waters GPC system, a Waters 1515 isocratic HPLC pump, a Waters 2414 refractive index detector, and a chromatographic column connected to an Olexis, Polypore, and mixed D column. The standard substance used was polymethyl methacrylate (PMMA STD), and the analysis was performed at 35°C at a flow rate of 1 mL / min.
[0172] <Weight Average Molecular Weight of Acrylic Silicone Resin>
[0173] The weight average molecular weight of the acrylic siloxane resin was measured as follows: using GPC (Waters GPC system, Waters 1515 isocratic HPLC pump, Waters 2414 differential refractometer), the GPC columns were 4 Shodex KF-801, 802.5, 803, 805 from Waters connected in series, the solvent was tetrahydrofuran (THF), and the measurement was performed at a rate of 1 mL / min.
[0174] 4) Modulus / elongation at break
[0175] According to ASTM D882, a polyamide-imide film having a length of 50 mm and a width of 10 mm was measured at 25° C. under a tensile condition of 50 mm / min using UTM 3365 manufactured by Instron.
[0176] The thickness of the film is measured and this value is entered into the instrument. The unit of modulus is GPa and the unit of elongation at break is %.
[0177] 5) Light transmittance
[0178] According to ASTM D1746, for a film having a thickness of 50 μm, the total light transmittance was measured in the entire wavelength region of 400-700 nm using a spectrophotometer (Nippon Denshoku, COH-400), and the single wavelength transmittance was measured at 388 nm using an ultraviolet / visible (UV / Vis) (Shimadzu, UV3600). The unit is %.
[0179] 6) Haze
[0180] The measurement was performed using a spectrophotometer (Nippon Denshoku Industries Co., Ltd., COH-400) based on a film having a thickness of 50 μm according to ASTM D1003. The unit is %.
[0181] 7) Yellowness Index (YI) and b* Value
[0182] The measurement was performed using a colorimeter (ColorQuest XE, manufactured by HunterLab) in accordance with ASTM E313, with a film having a thickness of 50 μm as a reference.
[0183] 8) Water contact angle
[0184] The contact angle was measured using a water contact angle meter (DSA, Kruss) according to ASTM D 5946.
[0185] 9) Pencil hardness
[0186] The film was subjected to pencil hardness measurement based on JIS K5400 by drawing a 20 mm line at a speed of 50 mm / sec with a load of 750 g five or more times and using the case where two or less scratches were generated.
[0187] 10) Measurement of warpage
[0188] Under constant temperature and humidity conditions of 25±3°C and 60±5% RH, a 10 cm×10 cm hard coating film is tilted 45° relative to the MD direction and left for 12 hours. Then, for the plane connecting each vertex, the vertical height (in mm) from the lowest position of the film (e.g., the center) to the plane connecting the vertices is measured, and the maximum value is taken as the warpage (mm).
[0189] 11) Evaluation of folding characteristics (dynamic bending characteristics)
[0190] The hard coating film was cut into a width of 100 mm and a length of 200 mm. According to IEC62715-6-1, it was fixed in a folding tester (YUASA) using an adhesive. The folding radius was set to 3 mm, and then the inward folding (inside the coating surface) test was repeated at a speed of 10 mm / second for 30,000 times, 100,000 times, and 200,000 times, and then the cracks in the folded part were visually confirmed. Whether fine cracks were generated was observed using a microscope.
[0191] [Preparation Example 1] Preparation of substrate layer
[0192] In a reactor, terephthaloyl chloride (TPC) and 2,2'-bis(trifluoromethyl)-benzidine (TFMB) were added to a mixed solution of dichloromethane and pyridine, and stirred at 25°C for 3 hours under a nitrogen atmosphere. At this time, the molar ratio of TPC:TFMB was set to 300:400, and the solid content was adjusted to 12% by weight. Thereafter, the reactant was precipitated in excess methanol, and then filtered to obtain a solid, which was vacuum dried at 50°C for more than 6 hours to obtain an oligomer, and the molecular weight (Formula Weight, FW) of the prepared oligomer was 1690 g / mol.
[0193] N,N-dimethylacetamide (DMAc) as a solvent, 100 mol of the oligomer, and 28.6 mol of 2,2′-bis(trifluoromethyl)-benzidine (TFMB) were added to the reactor and stirred sufficiently.
[0194] After confirming that the solid raw material was completely dissolved, fumed silica (surface area of 95 m 2 / g, <1μm) was added to DMAc, dispersed and added using ultrasound. 64.3 mol of cyclobutanetetracarboxylic dianhydride (CBDA) and 64.3 mol of 4,4'-hexafluoroisopropylidene diphthalic anhydride (6FDA) were added in sequence and stirred well, and then polymerized at 40°C for 10 hours. At this time, the solid content was 20% by weight. Next, 2.5 times the mole of pyridine and acetic anhydride were added to the solution in sequence relative to the total dianhydride content, and stirred at 60°C for 12 hours.
[0195] After the polymerization, the polymerization solution was precipitated in an excess of methanol and then filtered to obtain a solid, which was vacuum dried at 50° C. for more than 6 hours to obtain a polyamideimide powder. The powder was diluted and dissolved in DMAc to 20% to prepare a composition for forming a substrate layer.
[0196] The composition for forming a substrate layer was coated on a polyethylene terephthalate (PET) substrate film using an applicator, dried at 80°C for 30 minutes, dried at 100°C for 1 hour, and cooled at room temperature to produce a film. Thereafter, a stepwise heat treatment was performed at 100-200°C and at 250-300°C at a heating rate of 20°C / min for 2 hours.
[0197] The thickness of the manufactured polyamide-imide film is 50 μm, the transmittance at 388 nm is 15%, the total light transmittance is 89.73%, the haze is 0.4%, the yellowness index (YI) is 1.9, the b* value is 1.0, the modulus is 6.5 GPa, the elongation at break is 21.2%, the weight average molecular weight is 310000 g / mol, the polydispersity index (PDI) is 2.11, and the pencil hardness is HB / 750g.
[0198] [Preparation Example 2] Preparation of a composition for forming a hard coat layer
[0199] 3-Acryloxypropyltrimethoxysilane (APTMS, TCI) and water were mixed in a ratio of 24.64 g:2.70 g (0.1 mol:0.15 mol) and added to a 250 mL two-neck flask. Then, 0.1 mL of tetramethylammonium hydroxide catalyst and 100 mL of tetrahydrofuran were added to the mixture, and stirred at 25°C for 36 hours.
[0200] After that, the layers were separated, and the product layer was extracted with dichloromethane, the extract was dehydrated with magnesium sulfate, and the solvent was vacuum dried to obtain a resin. The weight average molecular weight of the acrylic siloxane resin was measured by gel permeation chromatography (GPC) and was 8100 g / mol.
[0201] A composition was prepared by mixing 30 g of the acrylic siloxane resin, 13 g of pentaerythritol tetraacrylate, 2 g of 1-hydroxy-cyclohexyl phenyl ketone as a photoinitiator, 5 g of a fluorine-based additive (DIC's Megaface RS90, fluorine-modified acrylate) and 50 g of methyl ethyl ketone.
[0202] [Preparation Example 3] Preparation of a composition for forming a hard coat layer
[0203] In the preparation example 2, the preparation was carried out by the same method as the preparation example 2 except that the contents of pentaerythritol tetraacrylate and fluorine-based additive (Megaface RS90 of DIC Corporation, fluorine-modified acrylate) were changed to 15 g.
[0204] [Preparation Example 4] Preparation of a composition for forming a hard coat layer
[0205] In the preparation example 2, no acrylic siloxane resin was used, and a composition was prepared by mixing 43 g of pentaerythritol tetraacrylate, 2 g of 1-hydroxy-cyclohexyl phenyl ketone as a photoinitiator, and 53 g of methyl ethyl ketone.
[0206] [Example 1]
[0207] The composition for forming a hard coating layer prepared in Preparation Example 2 was coated on one side of the polyamide-imide film prepared in Preparation Example 1 using a Meyer rod, and then cured at 60° C. for 5 minutes and heated with a high-pressure metal lamp at 1 J / cm 2 Ultraviolet rays (UV) were irradiated and then thermally cured at 120° C. for 15 minutes to form a hard coating layer having a thickness of 10 μm, thereby preparing a window covering film. Physical properties of the prepared window covering film were measured and are shown in Table 1 below.
[0208] [Example 2]
[0209] In Example 1, a hard coating layer was formed by the same method as in Example 1 except that the hard coating layer had a thickness of 3 μm, thereby preparing a window cover film. Physical properties of the prepared window cover film were measured and are shown in Table 1 below.
[0210] [Example 3]
[0211] In Example 1, a hard coating layer was formed by the same method as in Example 1, except that the composition for forming a hard coating layer prepared in Preparation Example 3 was used instead of the composition prepared in Preparation Example 2, thereby preparing a window cover film. The physical properties of the prepared window cover film were measured and are shown in Table 1 below.
[0212] [Comparative Example 1]
[0213] In Example 1, a hard coating layer was formed by the same method as in Example 1, except that the composition for forming a hard coating layer prepared in Preparation Example 4 was used instead of the composition prepared in Preparation Example 2, thereby preparing a window cover film. The physical properties of the prepared window cover film were measured and are shown in Table 1 below.
[0214] [Comparative Example 2]
[0215] In the Example 1, no hard coating layer was formed, and the physical properties of the polyamide-imide film having a thickness of 50 μm prepared in the Preparation Example 1 were measured and shown in Table 1 below.
[0216] [Comparative Example 3]
[0217] In Example 1, a window cover film was prepared by the same method as Example 1 except that a polyethylene terephthalate (PET) film having a thickness of 50 μm was used instead of the polyamideimide film prepared in Preparation Example 1. Physical properties of the prepared window cover film were measured and are shown in Table 1 below.
[0218] [Table 1]
[0219]
[0220]
[0221] As described above, the present invention is illustrated through specific contents and limited embodiments and drawings, but this is only provided to help a more comprehensive understanding of the present invention. The present invention is not limited to the above embodiments, and ordinary technicians in the field to which the present invention belongs can make various modifications and deformations through such descriptions.
[0222] Therefore, the concept of the present invention should not be limited to the described embodiments, and the claims of the present invention and all contents equivalent to the claims or having equivalent variations belong to the scope of the concept of the present invention.
Claims
1. A window covering film, comprising: a substrate layer formed of a polyamide-imide-based resin; A hard coating layer is formed directly on at least one side of the substrate layer. The dynamic friction coefficient measured on the hard coating layer using sulfuric acid paper as a friction material and under a load of 200 g, a force of 5 N, and a speed of 100 mm / min is less than 0.15, and the ratio of the static friction coefficient a to the dynamic friction coefficient b satisfies the following formula 1: [Formula 1] 1≤a / b≤1.2 wherein the substrate layer is formed of a polyamideimide (PAI)-based resin containing fluorine atoms and an aliphatic cyclic structure, and the hard coating layer is formed of a composition for forming a hard coating layer, wherein the composition for forming a hard coating layer contains a (meth)acrylic siloxane resin and a multifunctional (meth)acrylate-based compound, and The polyamideimide (PAI) based resin is prepared by the following steps: preparing an amine-terminated polyamide oligomer from a first fluorine-based aromatic diamine and an aromatic diacid chloride, polymerizing the amine-terminated polyamide oligomer with a monomer derived from a second fluorine-based aromatic diamine, an aromatic dianhydride and an alicyclic dianhydride, and performing imidization.
2. The window covering film according to claim 1, wherein: The static friction coefficient is 0.2 or less.
3. The window covering film according to claim 1, wherein: The dynamic friction coefficient is 0.1 or less.
4. The window covering film according to claim 1, wherein: The substrate layer has a modulus of 3 GPa or more according to ASTM D882, an elongation at break of 8% or more, a transmittance of 5% or more measured at 388 nm according to ASTM D1746 and a total light transmittance of 87% or more measured at 400-700 nm, a haze of 2.0% or less, a yellowness index of 5.0 or less, and a b* value of 2.0 or less.
5. The window covering film according to claim 1, wherein: The thickness of the substrate layer is 10-500 μm, and the thickness of the hard coating layer is 1-50 μm.
6. The window covering film according to claim 1, wherein: The hard coating layer has a pencil hardness of 4H or more and a water contact angle of 80° or more.
7. The window covering film according to claim 1, wherein: The warpage amount of each vertex of a square sample of the window cover film, which is a sample cut so that each side has a length of 10 cm and each side is inclined at an angle of 45° with respect to the MD direction of the film, is 5 mm or less.
8. The window covering film according to claim 1, wherein: When dynamic bending characteristics were evaluated, the window cover film did not generate cracks at 30,000 to 200,000 times.
9. A flexible display panel comprising the window covering film according to any one of claims 1 to 8.
Citation Information
Patent Citations
Plastic substrate
KR1020130074167A
Polyamic acid resin and polyamideimide film
CN109486188A
Low-color polymers for use in electronic devices
TW201920369A
Laminate and window film and electronic device
US20200061967A1